Conservative treatment of head and neck lymphoma is not the only effective treatment: A retrospective analysis of 301 cases. (May 2022) - Wen, Xutao; Hu, Yuhua; Liu, Yuan; Li, Zhengrui; Mai, Huaming; Zhang, Ling
Highlights: Non-Hodgkin's lymphoma, like MALT lymphoma, is the main type, which most often occurs in the glands. For aNHL, conservative treatments like radiation and chemotherapy are effective. For iNHL especially in glands, we can adopt wide local excision without other therapy. Abstract: Objectives: To study the influence of different treatments on the prognosis of patients with head and neck lymphoma (HNL). Materials and Methods: A single center retrospective study was conducted on 301 patients with HNL diagnosed from 2015 to 2020, compare the disease-free survival rate of patients treated surgically or conservatively. Results: For indolent non-Hodgkin's lymphoma (iNHL), there is no significant difference in the prolongation of disease-free survival time between surgery and conservative treatment (P > 0.05). Conclusion: For iNHL especially in glands, we can adopt wide local excision without other therapy.